Pendampingan PENDAMPINGAN PENCATATAN LAPORAN KEUANGAN SEDERHANABERBASIS MICROSOFT EXCEL UNTUK MENINGKATKAN PENGELOLAAN KEUANGAN DAN KESIAPAN KEPATUHAN PAJAK PADA UMKM KOPI DADAKAN - Yulita Permatasari (LP2M Politeknik Jambi, 2026)
This study aims to analyze the conditions of recording and preparing financial statements in Kopi Imduk MSMEs, identify financial management obstacles manually, and evaluate the effectiveness of assisting in the preparation of Microsoft Excel-based financial statements in improving the understanding of MSME actors in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) and tax compliance readiness. The study method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that before mentoring, financial recording of Kopi Dadakan MSMEs was still done manually and unstructured, is difficult for business owners to know profits and calculate tax obligations. Assistance in preparing of Microsoft Excel-based financial report has been proven to be able to assist MSME actors in recording transactions more systematically, accurately, and in accordance with the SAK EMKM. Besides that, the implementation of this system increases MSME actors' understanding of business financial conditions and provides an initial overview of the calculation of MSME Final Income Tax. Thus, this assistance contributes positively to improve financial management and tax compliance readiness for Kopi Imduk MSMEs.